Functional drug screening reveals anticonvulsants as enhancers of mTOR‐independent autophagic killing of Mycobacterium tuberculosis through inositol depletion. Issue 2 (22nd December 2014) - Schiebler, Mark; Brown, Karen; Hegyi, Krisztina; Newton, Sandra M; Renna, Maurizio; Hepburn, Lucy; Klapholz, Catherine; Coulter, Sarah; Obregón‐Henao, Andres; Henao Tamayo, Marcela; Basaraba, Randall; Kampmann, Beate; et al.
Abstract Mycobacterium tuberculosis (MTB) remains a major challenge to global health made worse by the spread of multidrug resistance. We therefore examined whether stimulating intracellular killing of mycobacteria through pharmacological enhancement of macroautophagy might provide a novel therapeutic strategy. Despite the resistance of MTB to killing by basal autophagy, cell‐based screening of FDA‐approved drugs revealed two anticonvulsants, carbamazepine and valproic acid, that were able to stimulate autophagic killing of intracellular M. tuberculosis within primary human macrophages at concentrations achievable in humans. Using a zebrafish model, we show that carbamazepine can stimulate autophagy in vivo and enhance clearance of M. marinum, while in mice infected with a highly virulent multidrug‐resistant MTB strain, carbamazepine treatment reduced bacterial burden, improved lung pathology and stimulated adaptive immunity. We show that carbamazepine induces antimicrobial autophagy through a novel, evolutionarily conserved, mTOR‐independent pathway controlled by cellular depletion of myo‐inositol. While strain‐specific differences in susceptibility to in vivo carbamazepine treatment may exist, autophagy enhancement by repurposed drugs provides an easily implementable potential therapy for the treatment of multidrug‐resistant mycobacterial infection.